(y + 6)(y+4) =

\(Y^{2}+10 y+24\)

Explanation

Take the variable in the first set times the first variable in the second set: \((y) y=y^{2}\). Then, take the first variable in the first set times the second variable in the second set: y(4) = 4y.
So far, we have: \(y^{2}+4 y\).
Now, take the second variable in the first set times the first variable in the second set: 6(y) = 6y. Now, we have: \(y^{2}+4 y+6 y\)
Finally, we have the second variable in the first set times the second variable in the second set: \(6 \times 4 = 24\)
\(y^{2}+4 y+6 y+24=y^{2}+10 y+24\)

Visit our website for other ASVAB topics now!